2017
DOI: 10.2147/ppa.s120464
|View full text |Cite|
|
Sign up to set email alerts
|

Patient satisfaction with cardiac rehabilitation: association with utilization, functional capacity, and heart-health behaviors

Abstract: BackgroundCardiac rehabilitation (CR) societies recommend assessment of patient satisfaction given its association with health care utilization and outcomes. Recently, the Patient Assessment of Chronic Illness Care (PACIC, Glasgow) was recommended as an appropriate tool for the CR setting. The objectives of this study were to 1) describe patient satisfaction with CR, 2) test the psychometric properties of the PACIC in the CR setting, and 3) assess the association of patient satisfaction with CR utilization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…The earlier study observed that client’s satisfaction level is positively linked with the enrolment of health insurance scheme which could be enhanced by maintaining a better patient-doctor relationship [ 17 ]. It has been noted that the satisfied patients often utilize more the healthcare services and followed the treatment regime properly [ 21 , 43 ], however poor quality of healthcare is often considered as a major source of dissatisfaction, particularly in CBHI programs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earlier study observed that client’s satisfaction level is positively linked with the enrolment of health insurance scheme which could be enhanced by maintaining a better patient-doctor relationship [ 17 ]. It has been noted that the satisfied patients often utilize more the healthcare services and followed the treatment regime properly [ 21 , 43 ], however poor quality of healthcare is often considered as a major source of dissatisfaction, particularly in CBHI programs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the studies focused on benefit packages as well as client experiences and satisfactions toward health care services organized by this scheme although clients’ satisfactions are as important measures of health system performance [ 17 , 18 ]. Patient satisfaction is an important indicator of health care quality and often associated with greater adherence to medical technology, health service utilization, and health outcomes [ 19 , 20 , 21 ]. Huy and colleagues observed that satisfaction has a significant impact on patient retention, patient loyalty and influences the efficient delivery of quality in health care [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 In addition, patients’ greater satisfaction with their cardiac care for those with all forms of atherosclerotic cardiac diseases has been shown to be associated with greater adherence and completion rates to their cardiac rehabilitation, greater physical activity, and lower depressive symptoms at discharge. 10 However, an earlier study has also noted inconsistent findings where better clinical outcomes were not associated with higher patient satisfaction scores. 11 …”
Section: Introductionmentioning
confidence: 94%
“…As reported elsewhere [30], there were some differences in the characteristics of participants retained at 2 years (N = 192) versus those lost-to-follow-up. With regard to sociodemographic characteristics, retained participants were more likely to self-report "North American" ethnocultural background compared to those lost to followup.…”
Section: Respondents Characteristicsmentioning
confidence: 56%